2017
DOI: 10.1590/s1677-5538.ibju.2015.0468
|View full text |Cite
|
Sign up to set email alerts
|

Validation of self - confidence scale for clean urinary intermittent self - catheterization for patients and health - caregivers

Abstract: Objective To validate a measurement instrument for clean intermittent self-catheterization for patients and health-caregivers.Material and Methods Methodological study of instrument validation performed at a Rehabilitation Center in a University hospital for patients submitted to clean intermittent self-catheterization and their health-caregivers. Following ethical criteria, data were collected during interview with nurse staff using a Likert question form containing 16 items with 5 points each: “no confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 13 publications
0
16
0
4
Order By: Relevance
“…However, inappropriate catheterization may lead to the occurrence of CIC-related complications such as pain, urethral trauma, hematuria, and lower urinary tract infection [3]. CIC application training is crucial in bringing in the patient him/herself or his/her caregiver the knowledge and skills related to the application in the right way [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, inappropriate catheterization may lead to the occurrence of CIC-related complications such as pain, urethral trauma, hematuria, and lower urinary tract infection [3]. CIC application training is crucial in bringing in the patient him/herself or his/her caregiver the knowledge and skills related to the application in the right way [4].…”
Section: Introductionmentioning
confidence: 99%
“…Temiz aralıklı kateterizasyonda hemşirenin rolü, hasta bireye ve/veya bakım vericisine uygulama becerisi kazandıracak eğitim ve rehberliği sağlamaktır 4,5 . Eğitim ile birlikte artan kendi kendine uygulama becerisi, bireyin yeniden bağımsızlığını kazanarak öz güvenini ve benlik saygısınıartıracak, normal günlük yaşam aktivitelerine dönüşü sağlayarak bireyin yaşam kalitesinin artmasını destekleyecektir [2][3] .…”
Section: Introductionunclassified
“…Bireyin kendi yeteneğini tanıması ve duygularının farkına varması olarak tanımlanan öz güven, kendi kendine TAK uygulama başarısını etkileyen önemli bir kavramdır 5,6 . Öz güven, kişinin, bir şey yapma ya da başarma becerisine ilişkin kendi yeteneklerine inancının bir ölçütü olarak, herhangi bir davranış ve eylemi gerçekleştirme isteğini arttırırken,aynı zamanda, korku ve utanç gibi duygularla savaşan, yüksek başarı beklentisi olarak da nitelendirilmektedir 5,7 .Temiz aralıklı kateterizasyona uyum sürecinde, hasta bireyin kendine güven duyması özerklik ve uygulama becerisinin kazanılmasını önemli ölçüde etkilemektedir. Bu nedenle, konuya ilişkin eğitim ve rehberliğin planlanmasında hasta bireyin uygulama becerisinin yanı sıra öz güvenin belirlenmesioldukça önemlidir 3,5 .…”
Section: Introductionunclassified
“…Up to 95% of patients with MMC have a neurogenic bladder resulting in uncoordinated voiding leading to hostile bladder pressures 2 . Clean intermittent catheterization (CIC) is an important intervention in the management of patients with neurogenic bladder 3 . There are several gaps in knowledge with regards to CIC therapy in patients with MMC.…”
Section: Introductionmentioning
confidence: 99%
“…Available validated measurement tools and questionnaires for patients on CIC target adult patients with MMC. The Self Confidence Scale for Clean Urinary Intermittent Self‐Catheterization for Patients and Health‐Caregivers (SCSCISC) is a 16‐question survey Likert scale that assesses healthcare providers and patients' self confidence in performing CIC 3 . A study conducted with the SCSCISC found that for individuals age 12 to 20 with spinal cord injury, patient confidence is related to education and follow‐up care 3 .…”
Section: Introductionmentioning
confidence: 99%